2013
DOI: 10.1208/s12249-013-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Stabilization of Diltiazem HCl Release from Matrices Made from Aged Polyox Powders

Abstract: Abstract. Matrices containing PEO fail to provide stable drug release profiles when stored at elevated temperatures for a period of time. The present study aims to stabilize diltiazem HCl release from matrices made from various molecular weights of polyox powders. To this end, various molecular weights of polyox with and without vitamin E (0.25, 0.5 and 1% w/w) were stored at 40°C for 0, 2, 4 and 8 weeks. The aged polyox powders were then mixed with the model drug at a ratio of 1:1 and compressed into tablets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
6
4
1
Order By: Relevance
“…The results of the current study also illustrated that using SMB in the semi-and poorly water-soluble drugs, such as theophylline and zonisamide, had completely different effect in the beginning of drug release in terms of stability in comparison with the fresh samples without this antioxidant, although drug release decreased as storage time increased. These results particularly are not correlated with the previous data published by Shojaee et al [32,36], who studied the role of sodium metabisulphite on the release rate of diltiazem hydrochloride from polyethylene oxide. This was also a disagreement with earlier data observed in the beginning of this study with propranolol HCl and the reason is given earlier.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The results of the current study also illustrated that using SMB in the semi-and poorly water-soluble drugs, such as theophylline and zonisamide, had completely different effect in the beginning of drug release in terms of stability in comparison with the fresh samples without this antioxidant, although drug release decreased as storage time increased. These results particularly are not correlated with the previous data published by Shojaee et al [32,36], who studied the role of sodium metabisulphite on the release rate of diltiazem hydrochloride from polyethylene oxide. This was also a disagreement with earlier data observed in the beginning of this study with propranolol HCl and the reason is given earlier.…”
Section: Discussioncontrasting
confidence: 97%
“…Moreover, results clearly demonstrated that sodium metabisulphite is a good candidate to prevent degradation in different molecular weight PEO in highly soluble drugs such as propranolol HCl (60 mg/ml). The observed results may be deemed expected, according to previous reports by Shojaee et al [32], and our data for both PEO 750 and 303 containing propranolol HCl showed faster release for aged tablets without sodium metabisulphite; on the other hand, drug release was controlled in the presence of this antioxidant. It is interesting to note that there is no any other previous research that studied the effect of SMB in sustained release matrices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other factors which may also affect the rate at which a drug is released from its hydrophilic gel matrix may include the formulation composition [105-108], the physiochemical properties of the drug and polymer [109][110][111][112][113][114] and the processing and compaction conditions [115][116][117]. All these factors can influence the choice of the polymer viscosity and chemistry used.…”
Section: Effect Of Food On Drug Relelasementioning
confidence: 99%
“…Hydrophilic matrices are commonly used as oral drug delivery systems and are being increasingly investigated for controlled-release applications because they combine the advantages of not only being easy to formulate but are also economical to produce (Heller et al, 1983;Nokhodchi et al, 2012;Shojaee et al, 2013). The formation of a hydrated viscous layer around the tablet provides a barrier to drug release by opposing penetration of water into the tablet and also movement of dissolved solutes out of the tablet matrix (Bamba et al, 1979;Ghori et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%